The Subject of Citizenship Education as Character Education of Primary School Students - Suci Ramadhani (International Journal of Students Education, 2024)
Character building is something necessity, because assessed capable make participant educate become smart, have Budi good manners and polite polite so that participant educate meaningful as member public good for himself alone nor public in a way general and broad. Moral and virtuous character education character sublime poured in eye lesson education citizenship ( PKn ) is implemented each level school. For overcome matter the need exists innovation in the learning process teach especially in learning Civics. Review results literature can form whole report or article or series related activities with method collecting library data, reading and taking notes, as well as manage material study can form part from article, thesis, dissertation, or grant proposal.In terms general, study literature is one of the step for solve problem with look for written source previously.In the article scientific this data collection is carried out with literature method. Based on results and Discussion can understood that Teacher innovation and creativity are needed in build character participant educate on learning education citizenship (PKn) especially for participants educate school base.